Early cardiac involvement in patients with hyperthyroidism evaluated by cardiac magnetic resonance feature tracking - Zhang, Yi; Jia, Yiming; Ge, Renbin; Luo, Qian; Zhao, Xiance; Xing, Xing; Liu, Fang; Zhang, Lei (Frontiers in Endocrinology, 2025)
BackgroundThis study aimed to investigate the feasibility of quantitative assessment of myocardial injury in the early stages of the disease by myocardial strain in patients with hyperthyroidism.Methods and resultsA total of 45 individuals in the hyperthyroid state with at least one index of cardiac involvement (e.g., cardiac symptoms, abnormal electrocardiogram, or abnormal cardiac biomarkers) and 26 healthy controls were subjected to cardiovascular magnetic resonance (CMR) to assess the left ventricular (LV) volumetry, LV mass index (LVMi), LV ejection fraction (LVEF), myocardial strain, and the total (TEF), passive (PEF), and active (AEF) left atrial (LA) emptying fractions. Patients with hyperthyroidism were classified into two categories according to the presence (n = 5) or absence (n = 40) of atrial fibrillation (AF). The LA reservoir, conduit, and booster strains were significantly impaired in all patients with hyperthyroidism (all p < 0.01). In contrast, the LA and LV ejection fractions, LVMi, and LV myocardial strain showed no significant differences between the cases without AF and the healthy controls (all p > 0.05). The LA-AEF and LVEF were significantly decreased in the hyperthyroidism cases with AF compared with the hyperthyroidism cases without AF, although no significant differences in the LA-TEF, PEF, and LVMi were detected. The receiver operating characteristic (ROC) curve analysis revealed superior diagnostic value for the LA reservoir strain, which distinguished hyperthyroidism cases from normal subjects with a sensitivity of 80.8% and a specificity of 80%.ConclusionsThe LA strain reliably differentiates early cardiac involvement between patients with hyperthyroidism and healthy controls, whereas volumetric parameters and ventricular myocardial strain fail to do so.